Faults and stratigraphic boundaries control evolution of the huge debris flows along the Jinjiang River, China - Liu, Zhuoya; Wen, Yi; Mao, Xianyin; Lv, Qianyong; Zeng, Kuisen; Zhang, Ming (Frontiers in Earth Science, 2023)
This paper investigates the controlling factors of evolution of debris flows along the Jinjiang River, which is located in an active orogen. The debris flows along the Jinjiang River are threatening the nomads and the pastures, the power station on the river and its workers. Remote sensing images, geological maps and field investigations were conducted to determine the distribution of lithologies, faults, and debris flows. Totally 82.2 km of river bank and 108 debris flows including 22 huge ones were investigated. The results indicate that the distribution of the huge debris flows is primarily controlled by either faults or boundaries between sedimentary rocks and basalt. Both the faults and the stratigraphic boundaries play crucial roles in the evolution of the huge debris flows along the river.The fractured zone of faults and stratigraphic boundaries provides loose resource materials for the debris flows and is a weak strip prone to be incised to be a debris flow valley. However, the lithology has relatively less impact on the evolution of the huge debris flows.